Memory and cognitive control in task switching. - Richter, F; Yeung, N (2012)
Cognitive control and memory are fundamentally intertwined, but interactions between the two have only recently received sustained research interest. In the study reported here, we used a novel paradigm to investigate how control influences memory encoding and, conversely, how memory measures can provide new insight into flexible cognitive control. Participants switched between classifying objects and words, then were tested for their recognition memory of items presented in this task-switching phase. Task switching impaired memory for task-relevant information but actually improved memory for task-irrelevant information, which indicates that control demands reduced the selectivity of memory encoding rather than causing a general memory decline. Recognition memory strength provided a robust trial-by-trial measure of the effectiveness of cognitive control that "predicted" earlier task-switching performance. It also revealed a substantial influence of bottom-up factors on between-task competition, but only on trials in which participants had to switch from one type of classification to the other. Collectively, our findings illustrate how cognitive control and bottom-up factors interact to simultaneously influence both current performance and future memory.